LIFE QUALITY IN PATIENTS WITH TERMINAL CHRONIC RENAL FAILURE AND NEPHROGENIC ARTERIAL HYPERTENSION ON DIALYSIS - R. N. Kildebekova; Y. S. Ishmetov; A. V. Dmitriev; B. S. Ishmetov (Российский кардиологический журнал, 2002)
Life quality in patients with terminal chronic renal failure and nephrogenic arterial hypertension on dialysis.